Effect of Anti-Sclerostin Therapy and Osteogenesis Imperfecta on Tissue-level Properties in Growing and Adult Mice While Controlling for Tissue Age - Sinder, Benjamin P. (Bone, 2016)
Bone composition and biomechanics at the tissue-level are important contributors to whole bone strength. Sclerostin antibody (Scl-Ab) is a candidate anabolic therapy for the treatment of osteoporosis that increases bone formation, bone mass, and bone strength in animal studies, but its effect on bone quality at the tissue-level has received little attention. Pre-clinical studies of Scl-Ab have recently expanded to include diseases with altered collagen and material properties such as Osteogenesis Imperfecta (OI). The purpose of this study was to investigate the role of Scl-Ab on bone quality by determining bone material composition and tissue-level mechanical properties in normal wild type (WT) tissue, as well as mice with a typical OI Gly→Cys mutation (Brtl/+) in type I collagen. Rapidly growing (3-week-old) and adult (6-month-old) WT and Brtl/+ mice were treated for 5 weeks with Scl-Ab. Fluorescent guided tissue-level bone composition analysis (Raman spectroscopy) and biomechanical testing (nanoindentation) were performed at multiple tissue ages. Scl-Ab increased mineral to matrix in adult WT and Brtl/+ at tissue ages of 2–4wks. However, no treatment related changes were observed in mineral to matrix levels at mid-cortex, and elastic modulus was not altered by Scl-Ab at any tissue age. Increased mineral-to-matrix was phenotypically observed in adult Brtl/+ OI mice (at tissue ages >3wk) and rapidly growing Brtl/+ (at tissue ages > 4wk) mice compared to WT. At identical tissue ages defined by fluorescent labels adult mice had generally lower mineral to matrix ratios and a greater elastic modulus than rapidly growing mice, demonstrating that bone matrix quality can be influenced by animal age and tissue age alike. In summary, these data suggest that Scl-Ab alters the matrix chemistry of newly formed bone while not affecting the elastic modulus, induces similar changes between Brtl/+ and WT mice, and provides new insight into the interaction between tissue age and animal age on bone quality.